City life in Africa anthropological insights - Werthmann, Katja 1964- (Routledge, 2023)
"This book introduces readers to the anthropology of urban life in Africa, showing what ethnography can teach us about African city dwellers' own notions, practices and reflections. Social anthropologists have studied city life in Africa since the early twentieth century. Their works have addressed a number of questions that are relevant until today: What happens to rural people who move to the city? What kinds of livelihoods do they pursue? How does city life affect moralities and practices connected with gender roles, marriage, parenthood and intergenerational relations? In which social situations are ethnic and other collective identifications relevant? How do people make a home in the city? What forms of authority and leadership become relevant in urban governance? How do people talk about city life? This book asks what anthropologists have come to learn about Africans' views on city life. It provides a critical acclaim of ethnographies in English, French and German and elucidates anthropology's contribution to understanding city life in Africa. It highlights the significance of female, African and Diaspora scholars for an emerging urban anthropology of Africa. The chapters are organized according to everyday activities of city dwellers: moving, connecting, governing, working, dwelling and wayfinding. The book will be an essential read for students and researchers of social anthropology, African and urban studies, but also for professionals in research and development organizations, thinktanks and other institutions concerned with urban Africa"--
Keywords: Stadtleben; Feldforschung; Subsaharisches Afrika; Cities and towns / Africa; City and town life / Africa; Africa / Social life and customs; Villes / Afrique; Vie urbaine / Afrique; Afrique / Murs et coutumes; Cities and towns; City and town life; Manners and customs; Africa